Determinants of Non-Farm Enterprise Participation Among Agricultural Households in the Philippines - Anabo, Ferdinand D. (Philippine Management Review; Vol 28 (2021), 2023)
Most empirical studies have focused on the non-farm labor component of the rural non-farm economy. But equally important are the non-farm enterprises in the rural economy. There is no clear picture of the non-farm enterprise participation (NFEP) of agricultural households in the Philippines. This study fills this gap by determining the prevalence and patterns of NFEP, and by identifying the factors affecting participation and size of non-farm enterprises among agricultural households. This study uses microdata from the 2015 Family Income and Expenditure Survey covering households whose main source of income is agriculture-related activities. Logit and ordinary least square regressions are used. Results show that one out of every five agricultural households engage in some form of non-farm enterprise. But such participation is considered limited and minimal per household. The contribution of the non- farm enterprise cannot be considered marginal in comparison to other sources. Participation in non-farm enterprises and the size/scale thereof are related to factors, such as age, education, marriage, family size, agricultural income, access to credit, cash support, access to basic utilities, access to communication, and main source of income. Policy interventions promoting non-farm enterprise are discussed.